Pathological tau activates nuclear factor‐kappa B (NF‐κB) and drives neuroinflammation. (20th December 2022) - Bhaskar, Kiran; Jiang, Shanya; Dadras, Somayeh; Hulse, Jonathan P; Tangavelou, Karthikeyan; Chisholm, Devon C; Mandell, Michael
Abstract: Background: Hyperphosphorylation and aggregation of tau is a pathological hallmark of Alzheimer's disease and related tauopathies. Pathologically modified tau (pTau) displays varying degree of gain‐of‐toxic functions, in addition to loss of its normal homeostatic function in neurons. Several prior studies have suggested occurrence of innate immune activation in brain regions that spatio‐temporally overlap with pTau burden in brains of various tauopathies. Recent studies have suggested that once tau is hyperphosphorylated and misfolded, the neurons tend to expel pTau to the extracellular space, which is taken up by other neurons and results in trans‐neuronal propagation of pTau. We made a compelling discovery that en route to other neurons, pTau can also interact with and serve as an initial trigger to lead to microglial activation and neuroinflammation (Cell Reports 2021). However, it is not unclear if pTau driven innate immune activation involve canonical NF‐κB pathway. Methods: First, we determined the levels of NF‐κB activation in autopsy brains of different tauopathies via Western blot analyses for markers of NF‐κB. Second, we performed bulk‐RNA sequence analyses of human primary microglia treated with paired‐helical filaments (PHFs) purified from human tauopathy brains. Third, we crossed PS19 mouse model of tauopathy to NF‐κB‐GFP‐Luciferase reporter mice (Luc) to generate PS19/Luc + mice and performed IVIS® live image analyses at different time points. Finally, we treated Luc expressing BV2 cells, primary microglia, and bone marrow derived macrophages (BMDMs) with pTau and validated nuclear localization of NF‐κB via Cellomics® high‐content microscopy. Results: Phosphorylated NF‐κB p65 (Ser536) levels were significantly high in the autopsy brains of Corticobasal degeneration (CBD), Progressive supranuclear Palsy (PSP) and Pick's disease (PiD) compared to healthy controls. RNA‐seq and bioluminescence analyses suggested human brain‐derived pTau induced NF‐κB activation in microglial cells and BMDMs. PS19/Luc + mice displayed increased NF‐κB activation with age. Conclusions: Together, these results suggest NF‐κB activation in the brains of human tauopathy and that pTau can directly activate NF‐κB in various model systems. Neutralization of pTau via immunotherapy and determining if it has any effect on NF‐κB activation is in progress.